PENGARUH PENANAMAN MODAL DALAM NEGERI DAN PENANAMAN MODAL ASING TERHADAP PENYERAPAN TENAGA KERJA DI SAMARINDA - Khairil Akbar; Gunadi Gunadi (Politeknik Negeri Samarinda, 2018)
Investment as a variable that affects the economy as a whole, especially in creating employment opportunities where the expansion of employment opportunities is one of the main problems in development, both in the past or present. To determine the effect of foreign investment and domestic investment on employment in Samarinda city. Through data on foreign investment and domestic investment on employment in Samarinda during 2013 until 2017. Then it will be analyzed using multiple regression analysis tools, then investment through domestic investment and foreign investors have a significant positive influence on employment, especially in the city of Samarinda, because with the changes in PMDN and PMA investments towards the increase in the number of workers . Secondary data obtained and discussed using multiple linear regression tools which are then reformulated into multiple regression estimation models. The analysis shows that investments in Foreign Investment and Domestic Investment have a significant impact on employment in Samarinda. Then after the calculation of partial investment, Foreign Investment has a greater impact on employment than Domestic Investment in Samarinda City. With the mining sector, trade and industry and other sectors need labor in their activities. The factors of production are one of the workers who participate in producing goods and services.Keywords: Domestic Investment, Foreign Investment, Labor